Healthcare workers' perceptions of how eHealth applications can support self-care for patients undergoing planned major surgery - Anna Granath; Kerstin Eriksson; Lotta Wikström (BMC, 2022)
Abstract Background In planned major surgery the duration of inpatient hospital care during the last decade has decreased because of a combination of different perioperative interventions. It is expected that patients can manage the needed pre- and postoperative self-care to a large extent on their own. This entails challenges to healthcare system to deliver appropriate information to patients in a safe and efficient manner. The aim of this study was therefore to describe healthcare workers' perceptions of how eHealth applications can support patients' self-care in relation to planned major surgery. Methods Semi-structured interviews were performed with sixteen healthcare workers from different disciplines. The interviews were transcribed and analysed using the phenomenography approach. Results Healthcare workers perceived both positive aspects and challenges with eHealth applications for self-care. eHealth applications can work as an information source, affect patients' understanding of self-care, improve patients' participation in self-care, streamline communication with healthcare professionals and improve patient safety during the pre- and postoperative period. The challenges included perceptions of that eHealth applications may have negative impact on personal interaction in care. eHealth applications may not be useful to all patients because of lack of equipment or knowledge and may increase patients' suffering if physical visits are replaced by digital solutions. Conclusions This study improves our understanding of healthcare workers' perceptions of how the use of self-care eHealth applications can support patients in performing pre- and postoperative self-care for major surgery. Access to appropriate and personalized information and instructions can improve patients' understanding of self-care and enhance the participation and safety of those who can afford and handle digital tools. All these aspects must be considered in future digital development of eHealth applications to guarantee a person-centered care.